Prevalence of Plaque Induced Gingivitis Among Dental Students in College of Dentistry, Hawler Medical University. - Zainab Salim Mahmood; Qehraman Ismayil Ahmed; Ahmed Luqman Saifullah (Erbil Dental Journal)
Background and objective: Gingival inflammation in response to bacterial plaque accumulation is considered the key risk factor for the onset of periodontitis. Dental students should present to patients as good role models in their oral health behavior. The study aimed to evaluate the prevalence of plaque induced gingivitis among dental students in Hawler Medical University college of dentistry.